Estimation of Ethanol in Marketed Mouthwashes by Gas Chromatography - Marvania, M.; Deshpande, S.; Bagade, S.; Shelke, M. (Asian Journal of Chemistry, 2017)
The present study was oriented towards gas chromatographic estimation of alcohol, as a quality control process. The determination of ethanol in alcoholic mouthwash is very essential to maintain the quality and efficacy. In this study simple and rapid gas chromatographic method was developed for determination of ethanol in mouthwash using packed column (15 % FFAP, 2 m × 0.125 inch) with detection by flame ionization detector (FID). The retention time of alcohol was found to be less than 6 min. The estimate of the standard deviation of the chromatography for duplicate injections is ± 0.02 %. This gas chromatography method determines ethanol separately from the other components of mouthwash that interfere in detection method and without distillation or chemical reaction. When large numbers of samples are analyzed, it reduces analysis time per sample and with adequate accuracy of estimation. The developed method was validated with various validation parameters viz. accuracy, precision, ruggedness, robustness and could be one of the rapid methods for quality control analysis of alcohol containing mouthwashes.